Brevibacillus brevis HNCS-1: a biocontrol bacterium against tea plant diseases - Yang, Wenbo; Yang, Hui; Bao, Xiaocun; Hussain, Mehboob; Bao, Qiang; Zeng, Zexuan; Xiao, Chun; Zhou, Lingyun; Qin, Xiaoping (Frontiers in Microbiology, 2023)
As a biocontrol bacteria, Brevibacillus has been the subject of extensive research for agricultural applications. Br. brevis HNCS-1, a bacterium isolated from tea garden soil, has antagonistic effect against five kinds of pathogens of tea diseases, such as Gloeosporium theae-sinensis, Elsinoe leucospira, Phyllosticta theae, Fusarium sp. and Cercospora theae. To determine the genetic characteristics implicated in the biocontrol mechanism, the genome sequence of HNCS-1 was obtained and analysed further (GeneBank CP128411). The HNCS-1 strain and 17 public Br. brevis were subjected to a phylogenetic analysis using orthologous genes organised into five clusters. A comparison of Br. brevis HNCS-1 protein encoding gene with those of other Br. brevis strains revealed 3,742 core genes. Curiously, only one non-ribosomal peptides synthetase (NRPS) gene cluster annotated as edeine is present in the core genes. After conducting a blast comparison, it was discovered further that the gene cluster of the HNCS-1 strain was highly similar to the previously identified edeine NRPS gene cluster. The bioactive metabolites of the HNCS-1 strain was identified by Liquid chromatography with UHPLC-MS/MS analysis. The results showed that edeine B and edeine A were the principal antibacterial peptides in the HNCS-1 strain.